HuR regulates cyclin A and cyclin B1 mRNA stability during cell proliferation - Wang, Wengong (Oxford University Press, 2000)
Colorectal carcinoma RKO cells expressing reduced levels of the RNA-binding protein HuR (ASHuR) displayed markedly reduced growth. In synchronous RKO populations, HuR was almost exclusively nuclear during early G(1), increasing in the cytoplasm during late G(1), S and G(2). The expression and half-life of mRNAs encoding cyclins A and B1 similarly increased during S and G(2), then declined, indicating that mRNA stabilization contributed to their cell cycle-regulated expression. In gel-shift assays using radiolabeled cyclin RNA transcripts and RKO protein extracts, only those transcripts corresponding to the 3′-untranslated regions of cyclins A and B1 formed RNA–protein complexes in a cell cycle-dependent fashion. HuR directly bound mRNAs encoding cyclins A and B1, as anti-HuR antibodies supershifted such RNA–protein complexes. Importantly, the expression and half-life of mRNAs encoding cyclins A and B1 were reduced in ASHuR RKO cells. Our results indicate that HuR may play a critical role in cell proliferation, at least in part by mediating cell cycle-dependent stabilization of mRNAs encoding cyclins A and B1.